2001
DOI: 10.1128/jb.183.19.5709-5717.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the Bacterium Streptococcus pneumoniae Strain R6

Abstract: Streptococcus pneumoniae is among the most significant causes of bacterial disease in humans. Here we report the 2,038,615-bp genomic sequence of the gram-positive bacterium S. pneumoniae R6. Because the R6 strain is avirulent and, more importantly, because it is readily transformed with DNA from homologous species and many heterologous species, it is the principal platform for investigation of the biology of this important pathogen. It is also used as a primary vehicle for genomics-based development of antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
621
2
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(655 citation statements)
references
References 54 publications
18
621
2
8
Order By: Relevance
“…The analysis of genome sequences has shown that many bacteria appear to have multiple, putative efflux pumps [6,7,8]. The activity of these pumps contributes to the high levels of antibiotic resistance exhibited by organisms such as Pseudomonas aeruginosa [9].…”
Section: Efflux Pumpsmentioning
confidence: 99%
“…The analysis of genome sequences has shown that many bacteria appear to have multiple, putative efflux pumps [6,7,8]. The activity of these pumps contributes to the high levels of antibiotic resistance exhibited by organisms such as Pseudomonas aeruginosa [9].…”
Section: Efflux Pumpsmentioning
confidence: 99%
“…The sequencing of genomes of similar composition remained fairly intractable. This resulted in the genome of B. subtilis being the only Firmicute genome sequence for almost five years, until those of the much smaller genomes of Staphylococcus aureus (Kuroda et al ., 2001) and Streptococcus pneumoniae (Hoskins et al ., 2001; Tettelin et al ., 2001) were published, followed by that of Bacillus anthracis strains of size equivalent to that of B. subtilis (Read et al ., 2002). …”
Section: Introductionmentioning
confidence: 99%
“…The roles of other glycosidases remain unknown, yet at least one-third of the pneumococcal genome encodes proteins involved in sugar transport, degradation, and processing, suggesting that carbohydrate metabolism has a central impact on pneumococcal biology (16,27,47). In the sequenced pneumococcal genome, several genes are annotated as sugar hydrolases (otherwise known as glycosidases); however, the importance of these in glycoprotein degradation is not known.…”
mentioning
confidence: 99%
“…Carbohydrates are the principal energy sources for the pneumococcus, and these must be obtained exclusively from its host (16). Although the pneumococcus is known to utilize a variety of free sugars through at least 14 sugar utilization operons (10), in the upper respiratory tract the concentration of free sugars is low (39).…”
mentioning
confidence: 99%